2013
DOI: 10.3989/scimar.03817.05a
|View full text |Cite
|
Sign up to set email alerts
|

The artisanal elasmobranch fishery of the Pacific coast of Baja California Sur, Mexico, management implications

Abstract: SUMMARY: Artisanal fisheries in Mexico account for approximately 40% of the total national catch. In 2009, Baja California Sur (BCS) had the second largest catch of elasmobranchs on the Mexican Pacific coast. This paper characterizes and describes the artisanal elasmobranch fishery of Pacific coast of BCS from 2000 to 2010. Sixty artisanal camps were documented, of which 45 targeted elasmobranchs, using primarily gillnets and longlines. We identified 52 elasmobranch species. Gillnetting accounted for 73.5% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 32 publications
1
16
2
4
Order By: Relevance
“…Resettlement in Baja was encouraged and incentivized by the federal government starting in the 1970s, following the decline of mainland fisheries [29]. Additionally, ephemeral, seasonal fishing camps are common in the region [30,31]. In this context defining a typical fishing "community" in Northwestern Mexico quickly becomes challenging, as socio-economic characteristics tend to be highly variable across sites.…”
Section: Small-scale Fisheries In Northwest Mexicomentioning
confidence: 99%
“…Resettlement in Baja was encouraged and incentivized by the federal government starting in the 1970s, following the decline of mainland fisheries [29]. Additionally, ephemeral, seasonal fishing camps are common in the region [30,31]. In this context defining a typical fishing "community" in Northwestern Mexico quickly becomes challenging, as socio-economic characteristics tend to be highly variable across sites.…”
Section: Small-scale Fisheries In Northwest Mexicomentioning
confidence: 99%
“…Additionally, ephemeral, seasonal fi shing camps are common (Cartamil et al 2011 ;Ramirez-Amaro et al 2013 ). In this context, a fi shing "community" on the Baja Peninsula may be hard to defi ne and delineate, and can be considered relatively heterogeneous in cultural and socio-economic form.…”
Section: Baja Peninsula Mexicomentioning
confidence: 99%
“…Because its visual acuity and ability to see bioluminescence would not depend mainly on melanin (Wang et al 2007, Sparks et al 2014, Gruber et al 2016, social interactions with other swell sharks would be possible as well, as was previously suggested for albino elasmobranchs with yellow-orange eyes, caught either in interspecific aggregations (De JesusRoldan 1990) or swimming alone, but with apparently healthy status (Clark 2002, Sandoval-Castillo et al 2006, Reum et al 2008, Lipej et al 2011, Bigman et al 2015, Wakida-Kusunoki 2015. The specimen of Cephaloscyllium ventriosum presented here was considered a mature female, according to Ramírez-Amaro et al (2013). Catching the specimen alive means that it has been able to survive in this environment and avoid predators, possibly by hiding in rocky crevices, which is known a typical behaviour of this fish (Nelson andJohnson 1970, Compagno et al 2005).…”
mentioning
confidence: 69%
“…This mass of water is characterized by a mean temperature of <22°C, a salinity of 34‰ * , and upwelling events that promote high levels of primary productivity (MolinaCruz 1984). Although the presence of the swell shark is considered as rare in the fishery landings of southern Baja California Peninsula (Ramírez-Amaro et al 2013), it can be found due to the suitable environmental conditions and food availability, during this specific time of the year (Molina-Cruz 1984). Albinism is an autosomal recessive disorder affecting the production of melanin and caused by the absence or defect of tyrosinase (Wang et al 2007, Bigman et al 2015.…”
mentioning
confidence: 99%